Clinical Diagnostic and Prognostic Potential of NDRG1 and NDRG2 in Hepatocellular Carcinoma Patients - Xu, Shaohua; Gao, Ruihuan; Zhou, Yidan; Yang, Ying; Zhang, Yi; Li, Qianyuan; Luo, Chunhua; Liu, Song-Mei (Frontiers in Oncology, 2022)
Background: Primary liver cancer is still the most common lethal malignancy. The N-myc downstream-regulated gene family (NDRG1-4) is a group of multifunctional proteins associated with carcinogenesis. However, systematic evaluation of the diagnostic and prognostic values of NDRG1 or NDRG2 expression in liver cancer is poorly investigated. Method: Gene expression matrix of liver hepatocellular carcinoma (LIHC) was comprehensively analyzed by “limma” and “Dseq2” R packages. Gene ontology (GO) and Gene set enrichment analysis (GSEA) were used to identify the biological functional differences. The single-sample GSEA (ssGSEA) was conducted to quantify the extent of immune cells infiltration. Finally, Clinical and prognosis information of LIHC patients were systematically investigated by using Kaplan-Meier analysis and logistic & Cox regression analysis. Results: Compared to normal tissues, NDRG1 expression was higher, while NDRG2 expression was lower in tumor tissues (P < 0.001). The area under the receiver operator characteristic curve (AUROC) of NDRG1 and NDRG2 for LIHC were 0.715 and 0.799, respectively. Kaplan–Meier analysis revealed that NDRG1 and NDRG2 were both independent clinical prognostic biomarkers for the overall survival (OS, P = 0.001 and 2.9e–06), progression-free interval (PFI, P = 0.028 and 0.005) and disease-specific survival (DSS, P = 0.027 and P < 0.001). The C-indexes and calibration plots of the nomogram suggested that NDRG1 and NDRG2 have an effective predictive performance for OS (C-index: 0.676), DSS (C-index: 0.741) and PFI (C-index: 0.630) of liver cancer patients. The mutation rate of NDRG1 in liver cancer reached up to 14%, and DNA methylation levels of NDRG1 and NDRG2 promoters had a significant correlation with clinical prognosis. Conclusions: The mRNA expression and DNA methylation of NDRG superfamily members shows the potential for LIHC diagnosis and prognosis via integrative analysis from multiple cohorts.